2017
DOI: 10.1016/j.colsurfb.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Kupffer cells to liposome accumulation in the liver

Abstract: The liver is a major barrier for site-specific delivery of systemically injected nanoparticles, as up to 90% of the dose is usually captured by this organ. Kupffer cells are thought to be the main cellular component responsible for nanoparticle accumulation in the liver. These resident macrophages form part of the mononuclear phagocyte system, which recognizes and engulfs foreign bodies in the circulatory system. In this study, we have compared two strategies for reducing nanoparticle accumulation in the liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 34 publications
6
63
2
Order By: Relevance
“…In this study, the potential protective effects of BiNPs against apoptotic (ethanol) and oxidative stress‐inducing (hydrogen peroxide) agents were assessed. Macrophages were chosen as an in vitro model of cell stress as the largest portion of intravenously administered nanoparticles (synthetic or biological) are internalized by circulating or resident macrophages 1,41–44. Moreover, macrophages play a major role in tissue regeneration and several studies have demonstrated that the depletion of these cells causes impaired tissue repair 45,46.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the potential protective effects of BiNPs against apoptotic (ethanol) and oxidative stress‐inducing (hydrogen peroxide) agents were assessed. Macrophages were chosen as an in vitro model of cell stress as the largest portion of intravenously administered nanoparticles (synthetic or biological) are internalized by circulating or resident macrophages 1,41–44. Moreover, macrophages play a major role in tissue regeneration and several studies have demonstrated that the depletion of these cells causes impaired tissue repair 45,46.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages were chosen as an in vitro model of cell stress as the largest portion of intravenously administered nanoparticles (synthetic or biological) are internalized by circulating or resident macrophages. [1,[41][42][43][44] Moreover, macrophages play a major role in tissue regeneration and several studies have demonstrated that the depletion of these cells causes impaired tissue repair. [45,46] Cell viability studies demonstrated that both Lipo-NPs and ADSC-EVs protected macrophages from hydrogen peroxide ( Figure 4A) and ethanol-induced stress ( Figure 4B) to a similar extent.…”
Section: Protective Effects Of Lipo-nps and Adsc-evs In Macrophagesmentioning
confidence: 99%
“…Kupffer cells (that represent 80-90% of total body macrophages) are responsible for the most part of phagocytic activity in the liver. Kupffer cells, together with blood-circulating monocytes and splenic (red pulp and marginal zone) macrophages, constitute the mononuclear phagocyte system (MPS), which is responsible for the sequestration of more than 95% of NPs which consequently fail to reach their specific target [21,22]. e uptake rate of NPs depends strongly on size, surface charge and ligand chemistry, and shape.…”
Section: Mechanisms Involved In the Hepaticmentioning
confidence: 99%
“…Moreover, increasing the length of PEG (30 kDa) allowed vectors to evade KC scavenging (Prill et al, ). However, approaches looking into depletion of KCs or impeding receptors mediating uptake, displayed little impact on the cell‐mediated accumulation of NPs (Park et al, ; Samuelsson, Shen, Blanco, Ferrari, & Wolfram, ). Such findings denote that other cells in the hepatic microenvironment may also play a contributing role in liver sequestration of NPs.…”
Section: Cellular Interactions With Hepatic Cellsmentioning
confidence: 99%